The Role of Reflective Practitioner Heuristic Inquiry in Institutional learning and Research - Wong, E.S.K. (Macrothink Institute, 2010)
In this paper, the author reports on a critical and reflective practitioner heuristic inquiry that investigates a case study concern a post-modern approach in enhancing institutional teaching and research involving adult learning. In addition, the author investigates the research process itself and his own professional academic practices. Of particular interest is that this paper offers practitioners and teachers a new way of thinking about and pursuing concerns about a foray into many different disciplines, among these are sociology, education, business, strategic decision making, knowledge management, organisational theory, and current critical schools of thought, such as the work of Michel Foucault.